Radiopacity of endodontic materials using two models for conversion to millimeters of aluminum - Ochoa-Rodríguez, Victor Manuel [UNESP]; Wilches-Visbal, Jorge Homero; Roma, Barbara [UNESP]; Coaguila-Llerena, Hernán [UNESP]; Tanomaru-Filho, Mário [UNESP]; Gonçalves, Andréa [UNESP]; Spin-Neto, Rubens; Faria, Gisele [UNESP] (FapUNIFESP (SciELO), 2020)
The aims of the present study were to compare conventional radiography, radiographs digitized with a scanner or photographic camera, and digital radiography, used to evaluate the radiopacity of endodontic materials, and to compare the accuracy of linear and quadratic models used to convert radiopacity values to equivalent millimeters of aluminum (mm Al). Specimens of AH Plus, Endofill, Biodentine and BioMTA materials (n = 8) were radiographed next to an aluminum step-wedge using radiographic films and digital radiography systems (FONA CMOS sensor, Kodak CMOS sensor and photosensitive phosphor plate-PSP). Conventional radiographs were digitized using a scanner or photographic digital camera. Digital images of all the radiographic systems were evaluated using dedicated software. Optical density units (ODU) of the specimens and the aluminum step-wedge were evaluated by a photo-densitometer (PTDM), used in conventional radiographs. The radiopacity in equivalent mm Al of the materials was determined by linear and quadratic models, and the coefficients of determination (R2) values were calculated for each model. Radiopacity of the materials ranged from-9% to 25% for digital systems and digitized radiographs, compared to the PTDM (p < 0.05). The R2 values of the quadratic model were higher than those of the linear model. In conclusion, the FONA CMOS sensor showed the lowest radiopacity variability of the methodologies used, compared with the PTDM, except for the BioMTA group (higher than PTDM). The quadratic model showed higher R2 values than the linear model, thus indicating better accuracy and possible adoption to evaluate the radiopacity of endodontic materials.
Keywords: Dental; Dental cements; Digital; Endodontics; Materials testing; Radiography; Radiology